Konsistensi Model Zmijewski dalam Memprediksi Financial Distress: Peran Leverage, Likuiditas dan Profitabilitas - Herdiawan, Vicki; Okchatamsi, Dian (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Financial distress refers to a weakening financial condition that should be identified as early as possible to support better decisions by management, investors, and creditors. This study examines the consistency of the Zmijewski model in detecting financial distress in manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2025. The study also evaluates the roles of leverage, liquidity, and profitability in explaining distress risk. Leverage is represented by Debt to Equity Ratio (DER), liquidity by Current Ratio (CR), and profitability by Return on Assets (ROA). ROA is further treated as a moderating variable to assess whether profitability changes the relationship between DER and CR and financial distress. This research uses a descriptive quantitative approach with purposive sampling involving 25 manufacturing firms. The data were obtained from financial statements available through the Indonesia Stock Exchange. The findings show that DER has a positive and significant effect on financial distress, while CR and ROA have negative and significant effects. The moderation analysis indicates that ROA moderates the effect of DER on financial distress but does not moderate the effect of CR. These results imply that profitability is essential in reducing the distress risk created by leverage in manufacturing companies.